As obras “Bicho” e “Trepante” da artista Lygia Clark: materiais e técnicas construtivas - João Henrique Ribeiro Barbosa (2022)
This research has as its theme the detailed study of a selection of works of Lygia Clark (1922-1988) from the series Bicho and Trepante with the purpose to the preservation of Brazilian modern art. These works were produced in the 60s and were manipulated by the public, according to the innovative proposal conceived by the artist. Currently, for conservation reasons, this proposal is no longer developed. The Bicho e Trepante series presents several challenges for preservation: the introduction of new materials whose agents of deterioration are still unknown; the adaptation of industrial construction methods; the absence of dating and signature on the works; the joint performance of the artist with manufacturers; and the use of different terminologies for the description of the works (models, versions, multiples, and replicas). Therefore, this research proposes to: investigate the artist's motivations for the use of modern metal alloys; identify the metallic elements present in the works through Energy Dispersion X-Ray Fluorescence Spectroscopy equipment; point out the techniques used by the artist; evidence the changes presented by the works; and suggest procedures for the preservation of works. The methodology consisted in historical and bibliographic research; visual inspection visual examination of the works aiming to evidence techniques used in their confection, XRF analysis to identify the constituent materials and visual examination to identify possible signs of deterioration. Therefore, six works were selected: “O Antes é o depois” (1963) and “Trepante” (1965), both in stainless steel; “Bicho relógio de sol” (1960) and “Bicho máquina” (1962) in yellow anodized aluminum; and “Bicho relógio de sol” (1960), “Bicho” (1960), “Bicho” (1963) in aluminum. One of the research results indicates that the artist elaborated her artworks, but she also had the skill of national and international manufacturers; they made machines and instruments. In addition, it was possible to identify the presence of aluminum alloy in all the “Bichos” and stainless steel alloy in “Trepante”. The external appearance of both alloys is similar. Still, it is possible to distinguish both according to visual criteria such as the general shape of the work, sheet thickness, type of polishing, and assembly technique. Finally, a glossary and an overview of the risks associated with each damage was made, as well as recommendations for handling, display, and cleaning. In this way, it is possible to affirm that the study of materials and techniques in the series Bicho e Trepante by the artist Lygia Clark allows us to recognize the uniqueness of each work, proposing measures for its preservation.